Introducing a flexible drug delivery system based on poly(glycerol sebacate)-urethane and its nanocomposite: potential application in the prevention and treatment of oral diseases. Issue 4 (4th March 2022) - Tirgar, Mahtab; Hosseini, Hadi; Jafari, Milad; Shojaei, Shahrokh; Abdollahi, Amir; Jafari, Aliakbar; Uzun, Lokman; Goodarzi, Vahabodin; Su, Chia-Hung
Abstract: In this study, a novel biopolymer based on poly(glycerol sebacic)-urethane (PGS-U) and its nanocomposites containing Cloisite@30B were synthesized by facile approach in which the crosslinking was created by aliphatic hexamethylene diisocyanate (HDI) at room temperature and 80 °C. Moreover, metronidazole and tetracycline drugs were selected as target drugs and loaded into PGSU based nanocomposites. A uniform and continuous microstructure with smooth surface is observed in the case of pristine PGS-U sample. The continuity of microstructure is observed in the case of all bionanocomposites. XRD result confirmed an intercalated morphology for PGSU containing 5 wt% of clay nanoparticles with a d-spacing 3.4 nm. The increment of nanoclay content up to 5%, the ultimate tensile stress and elastic modulus were obtained nearly 0.32 and 0.83 MPa, which the latter was more than eight-fold than that of pristine PGS-U. A sustained release for both dugs was observed by 200 h. The slowest and controlled drug release rate was determined in the case of PGSU containing 5 wt% clay and cured at 80 °C. A non-Fickian diffusion can be concluded in the case of tetracycline release via PGS-U/nanoclay bionanocomposites, while a Fickian process was detected in the case of metronidazole release by PGS-U/nanoclay bionanocomposites. As a result, the designed scaffold showed high flexibility, which makes it an appropriate option for utilization in the treatment of periodontal disease. GRAPHICAL ABSTRACT: UF0001